Perceptions of racial discrimination and parenting reactions. The case of mixed Sub-Saharan African-Italian families in northern Italy. - (:unkn) unknown (My University, 2021)
This chapter discusses the parenting experience within mixed Sub-Saharan African-Italian families with regard to racial discrimination in postcolonial Italy. Based on analysis of semi-structured and narrative interviews conducted with 19 families consisting of one Sub-Saharan African parent (who emigrated to Italy as an adult) and one Italian parent in the north of Italy, this paper examines the correlations between family members’ experiences of discrimination and parents’ reactions. Focusing on the discrimination encountered by one of the parents, and on the couple’s reaction to it, enables a better understanding of the parents’ response to the discrimination encountered by their children. The findings highlight the roles of the migratory experience, socio-economic status, gender and phenotypic diversity in the parenting experience. The chapter contributes to the literature by showing that African-Italian families living in the postcolonial Italian context are at the centre of a relationship of domination, and must cope with this by deploying attitudes aimed at promoting their children’s integration with this society.
Keywords: African Research